Superior nasolabial flap in reconstruction of the tongue: case report - Munjal, Manish; Garg, Ramneesh; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham; Talwar, Shivam; Sharma, Salony; Kaur, Hardeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Hemiglossectomy with functional rehabilitation using a rotational superior nasolabial flap as a single stage procedure and its outcome has been described. Nasolabial sulcus and nasofacial was the donor site for the nasolabial flap. This hairless area except for the lower cheek in males, is an important consideration in oral cavity reconstruction. The flap constituted by skin, subcutaneous tissue and the underlying musculature has a subdermal plexus is supplied by feeder vessels from the branches of the facial artery and provides the blood supply to the nasolabial muscle and skin. Usually, the choice of pedicle is based on the site of the defect and any need for rotation or advancement of tissue to the site of the defect. In our patient the superior nasolabial flap based on alar and lateral nasal artery was utilized.